2018
DOI: 10.3389/fmicb.2018.01427
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal and Immunomodulatory Activities of the Palladacycle Complex DPPE 1.1, a Potential Candidate for Treatment of Cutaneous Leishmaniasis

Abstract: The present study focused on the activity of the palladacycle complex DPPE 1.1 on Leishmania (Leishmania) amazonensis. Promastigotes of L. (L.) amazonensis were destroyed in vitro by nanomolar concentrations of DPPE 1.1, whereas intracellular amastigotes were killed at drug concentrations fivefold less toxic than those harmful to macrophages. L. (L.) amazonensis-infected BALB/c mice were treated by intralesional injection of DPPE 1.1. Animals treated with 3.5 and 7.0 mg/kg of DPPE 1.1 showed a significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…It is reported that aziridine-2,3-dicarboxylate [180], natural products flavone derivatives [181], trans-aziridine-2,3-dicarboxylate derivatives [182] organotellurane RF07 and palladacycle complex [183][184][185], and dipeptidyl enoates [186] exhibit antileishmanial effect and inhibit cysteine proteases.…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…It is reported that aziridine-2,3-dicarboxylate [180], natural products flavone derivatives [181], trans-aziridine-2,3-dicarboxylate derivatives [182] organotellurane RF07 and palladacycle complex [183][184][185], and dipeptidyl enoates [186] exhibit antileishmanial effect and inhibit cysteine proteases.…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…Hence, host directed therapies, which directly modulate the immune response against parasites could be novel treatments for different forms of CL. Efficacy of immunomodulators in the treatment of CL has not only been demonstrated in experimental animal studies ( Buates and Matlashewski, 1999 ), but also in patients ( Chouhan et al., 2014 ; Dos Santos et al., 2018 ; Caridha et al., 2019 ; Nahidi et al., 2021 ). Immunotherapy can also be a suitable option for patients with clinical resistance to recommended drugs; for example, patients from Peru with resistance to antimony showed a faster resolution of CL lesions after the use of the TLR7 agonist imiquimod ( Miranda-Verástegui et al., 2005 ).…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…The activity of two palladacycle complexes, DPPE 1.1 and DPPE 1.2, was previously demonstrated on in vitro and in vivo L. (L.) amazonensis infection (14,15). The leishmanicidal effect of these palladacycle complexes is followed by activation of immune responses mediated by an increase of CD4 + and CD8 + T lymphocytes in treated animals (15,16).…”
Section: Introductionmentioning
confidence: 95%
“…The activity of two palladacycle complexes, DPPE 1.1 and DPPE 1.2, was previously demonstrated on in vitro and in vivo L. (L.) amazonensis infection (14,15). The leishmanicidal effect of these palladacycle complexes is followed by activation of immune responses mediated by an increase of CD4 + and CD8 + T lymphocytes in treated animals (15,16). A significant increase in the leishmanicidal effect of DPPE 1.2 as well as of inflammatory responses was observed when this palladacycle complex was associated with heat-killed-P. acnes suspension for treatment of L. (L.) amazonensisinfected BALB/c and C57BL/6 mice (16).…”
Section: Introductionmentioning
confidence: 97%